The role of body and environment in cognition - Dermot Lynott (Frontiers Research Topics, 2014)
Recent evidence has shown many ways in which our bodies and the environment influence cognition. In this Research Topic we aim to develop our understanding of cognition by considering the diverse and dynamic relationship between the language we use, our bodily perceptions, and our actions and interactions in the broader environment. There are already many empirical effects illustrating the continuity of mind- body-environment: manipulating body posture influences diverse areas such as mood, hormonal responses, and perception of risk; directing attention to a particular sensory modality can affect language processing, signal detection, and memory performance; placing implicit cues in the environment can impact upon social behaviours, moral judgements, and economic decision making. This Research Topic includes papers that explore the question of how our bodies and the environment influence cognition, such as how we mentally represent the world around us, understand language, reason about abstract concepts, make judgements and decisions, and interact with objects and other people. Contributions focus on empirical, theoretical, methodological or modelling issues as well as opinion pieces or contrasting perspectives. Topic areas include, perception and action, social cognition, emotion, language processing, modality-specific representations, spatial representations, gesture, atypical embodiment, perceptual simulation, cognitive modelling and perspectives on the future of embodiment.